Coupled fuel performance calculations in VERA and demonstration on Watts Bar unit 1, cycle 1. (15th September 2020) - Stimpson, S.; Clarno, K.; Pawlowski, R.; Gardner, R.; Powers, J.; Collins, B.; Toth, A.; Novascone, S.; Pitts, S.; Hales, J.; Pastore, G.
Highlights: A high fidelity, two-way coupling is presented between MPACT/CTF and Bison. This capability can be used to assess the importance of tight/loose coupling. Allows for insight into the fuel performance physics through VERA simulations. Cycle 1 of Watts Bar Nuclear Unit 1 are highlighted, emphasizing performance and comparing accuracy. Abstract: As the core simulator capabilities in the Virtual Environment for Reactor Applications (VERA) have become more mature and stable, increased attention has been focused on coupling Bison to provide fuel performance simulations. This technique has been a very important driver for the pellet-clad interaction challenge problem being addressed by the Consortium for Advanced Simulation of Light Water Reactors (CASL). In this article, two coupling approaches are demonstrated on quarter core problems based on Watts Bar Nuclear Plant Unit 1, Cycle 1: (1) an inline approach in which a one-way coupling is used between neutronics/thermal hydraulics (through MPACT/CTF) and fuel performance (through Bison) but no fuel temperature information is passed back to MPACT/CTF, and (2) a two-way approach (coupled) in which the fuel temperature is passed from Bison to MPACT/CTF. In both approaches, power and temperature distributions from MPACT/CTF are used to inform the Bison simulations for each rod in the core. The demonstrations presented here are the first integrated fuel performance simulations in VERA, which opens many possibilities for future work, including applications to accident-tolerant fuel efforts and transient simulations, which are of critical importance to CASL. These demonstrations also highlight the potential to move away from the current Bison-informed fuel temperature lookup table approach, which is the default in MPACT/CTF simulations, if performance improvements are made in the near future.